Practitioner Profile: An Interview with Syble Solomon - Syble Solomon (Journal of Financial Therapy, 2016)
Syble Solomon is a speaker on the psychology of money and the founder and president of LifeWise Strategies. She is best known for Money Habitudes® a deck of cards (and now an online version) that makes it easy to talk about money and discover what motivates our financial behaviors. Before becoming interested in why people manage money as they do, she had careers in early childhood special education, gerontology and executive coaching. Seemingly unrelated, they all provided experience training, developing educational material and empowering people at all socio-economic levels to work through challenging times and transitions. An excellent background for helping people work through money-related issues!
Keywords: financial therapy; money habits; money habitudes; financial tools